Penegakan Restorative Justice Terhadap Anak Korban Kejahatan Tindak Pidana Penganiayaan di Kota Batam - Natasha Fraiskam; Lu Sudirman; Rina Shahriyani Shahrullah (Jurnal Ilmu Hukum, Humaniora dan Politik, 2024)
The crime of maltreatment often occurs and is spread through social media or direct observation, including in Indonesia, including in small cities such as Batam City. Maltreated children suffer from psychological and physical effects, such as physical, emotional, and sexual abuse, which frequently takes place in public settings such as households, schools, and other locations. Among the traits of restorative justice are its emphasis on future accountability, use of discussion and negotiation as the normative foundation, and healing-oriented approach. This study, which employs an empirical legal and social methodology, looks at how Batam City handles child abuse crimes and considers restorative justice. The primary and secondary data make up the research object. Interviewing connected parties in-depth yields primary data, such as the prosecutor's office, police, victims, women and children's offices, and judges. Meanwhile, secondary data involved primary legal materials, such as the 1945 Constitution, Criminal Code, Juvenile Justice System Law, Child Protection Law, in addition, additional legal materials in the form of books and scientific publications, as well as prosecution and police regulations for discontinuation of prosecution based on restorative justice and treatment of criminal cases based on the same principles. The findings and conclusions of this study indicate that the Batam City government and law enforcement organizations strongly believe in the application of restorative justice. Although it faces challenges and differences in views, the hope is to provide long-term benefits for the community, victims and perpetrators, so that restorative justice in Batam City becomes a progressive step in responding to violence against children.